2022
DOI: 10.21203/rs.3.rs-1500697/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiplexed measurement of binding- and neutralizing antibodies to SARS-CoV-2 variants in 12.000 post-vaccine sera

Abstract: Diagnostic assays currently used to monitor the efficacy of COVID-19 vaccines measure levels of antibodies to the receptor-binding domain of ancestral SARS-CoV-2 (RBDwt). However, the predictive value for protection against new variants of concern (VOCs) has not been firmly established. Here, we used bead-based arrays and flow cytometry to measure binding of antibodies to spike proteins and receptor-binding domains (RBDs) from VOCs in 12,000 sera. Effects of sera on RBD-ACE2 interactions were measured as a pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Assessments of immunogenicity were performed at the Department of Immunology at Oslo University Hospital. The samples were first screened for antibodies to RBD at the full‐length spike protein by using an in‐house bead‐based method, with seroconversion defined as an anti‐RBD antibody level ≥5 AU ( 25 , 26 ). Measurement of the World Health Organization international standard for anti‐RBD antibody showed that the screening assay has a lower detection limit of 1 binding antibody unit per milliliter (BAU/ml) and an upper dynamic range of ~100 BAU/ml.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessments of immunogenicity were performed at the Department of Immunology at Oslo University Hospital. The samples were first screened for antibodies to RBD at the full‐length spike protein by using an in‐house bead‐based method, with seroconversion defined as an anti‐RBD antibody level ≥5 AU ( 25 , 26 ). Measurement of the World Health Organization international standard for anti‐RBD antibody showed that the screening assay has a lower detection limit of 1 binding antibody unit per milliliter (BAU/ml) and an upper dynamic range of ~100 BAU/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of the World Health Organization international standard for anti‐RBD antibody showed that the screening assay has a lower detection limit of 1 binding antibody unit per milliliter (BAU/ml) and an upper dynamic range of ~100 BAU/ml. For quantification of antibody levels, most patient samples and a representative selection of control samples (Supplementary Table 1 ) were thereafter analyzed using a second assay, with a dynamic range of 300–10,000 BAU ( 25 ). In this assay, effects of sera on binding of angiotensin‐converting enzyme 2 to RBDs from SARS–CoV‐2 variants were measured as a proxy for neutralizing antibody activity ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on in vitro neutralizing assays in our lab, and in line with Dimeglio et al, we have defined 200 BAU/ml as a cut‐off for neutralizing activity against ancestral SARS‐CoV‐2 and 11 000 BAU/ml as a cut‐off for neutralization against the Omicron‐variant. 2 , 3 Observational data after dose 3 registered in the Norwegian Renal Registry indicate >200 BAU/ml as clinically “protective” against the delta variant of concern. Neutralizing effect following dose 4 is presented in Figure 1 .…”
Section: Tablementioning
confidence: 99%
“…The dot plots show accumulated data for 188 patients, and each dot corresponds to a different serum. Bead‐based arrays were incubated with sera diluted at 1:100 and then labeled with fluorochrome‐conjugated anti‐human IgG or recombinant ACE2 (Tran et al 2 ).…”
Section: Tablementioning
confidence: 99%